2001
DOI: 10.1046/j.0305-1846.2001.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of adrenomedullin, leptin, their receptors and neuropeptide Y in hormone‐secreting and non‐functioning pituitary adenomas, meningiomas and malignant intracranial tumours in humans

Abstract: The aim of this study was to assess human intracranial tumours for their gene expression pattern of the vasoactive peptide adrenomedullin (AM), its receptor (AM-R) and leptin, which exerts multiple biological effects including proliferation and angiogenesis via the leptin receptor (OB-Rb). Gene activity of neuropeptide Y (NPY) was monitored additionally. We investigated whether there was a characteristic gene expression pattern of AM and leptin in different intracranial tumours, depending on their proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
1
23
1
Order By: Relevance
“…Another study found lower degrees of proNPY processing to NPY in tumor tissue were correlated to advanced clinical stages and poor outcome in neuroblastomas (Bjellerup et al, 2000). However, Knerr et al(2001) investigated a series of intracranial tumors and demonstrated that well-differentiated tumors (such as grade I astrocytomas) exhibit higher levels of NPY than anaplastic tumors. The importance of NPY in the prostate carcinoma is rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found lower degrees of proNPY processing to NPY in tumor tissue were correlated to advanced clinical stages and poor outcome in neuroblastomas (Bjellerup et al, 2000). However, Knerr et al(2001) investigated a series of intracranial tumors and demonstrated that well-differentiated tumors (such as grade I astrocytomas) exhibit higher levels of NPY than anaplastic tumors. The importance of NPY in the prostate carcinoma is rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 ADM gene expression and peptide production could be demonstrated in many types of normal and also in neoplastic cells. [7][8][9][10] ADM binding sites are also found in various tissues; a shared receptor with calcitonin gene-related peptide (CGRP) could be characterized further as being regulated by specific receptor activity modifying proteins (RAMPS). 11 ET-1 stimulates ADM expression in vascular smooth muscle cells (VSMC) as do the inflammatory cytokines, but the regulation profiles of these vasoactive substances are rather complex.…”
Section: Introductionmentioning
confidence: 99%
“…The local synthesis of leptin is supported by the presence of leptin mRNA, in rat and mouse pituitaries, and in human pituitary adenomas (Morash et al 1999, Jim et al 2000, Knerr et al 2001, Korbonits et al 2001. Additionally, in rat and mouse pituitaries, thyrotrophs and other pituitary cells express leptin and leptin receptors (Morash et al 1999, Jim et al 2000, Korbonits et al 2001, Knerr et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of leptin receptor in the human (Jim et al 1999, Knerr et al 2001, Korbonits et al 2001 and rat (Jim et al 2000, Sone et al 2001 pituitary gland raises the possibility that circulating leptin might also act directly to modulate TSH release. It has been shown that leptin regulates secretion of other pituitary hormones from isolated glands or cell cultures (Casanueva & Dieguez 1999).…”
Section: Introductionmentioning
confidence: 99%